2020
DOI: 10.1016/j.stemcr.2020.09.010
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Reprogramming Ameliorates Aging Features in Dentate Gyrus Cells and Improves Memory in Mice

Abstract: Post-translational epigenetic modifications take place in mouse neurons of the dentate gyrus (DG) with age. Here, we report that agedependent reduction in H3K9 trimethylation (H3K9me3) is prevented by cyclic induction of the Yamanaka factors used for cell reprogramming. Interestingly, Yamanaka factors elevated the levels of migrating cells containing the neurogenic markers doublecortin and calretinin, and the levels of the NMDA receptor subunit GluN2B. These changes could result in an increase in the survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
73
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 50 publications
14
73
0
5
Order By: Relevance
“…Through epigenetic reprograming some never before thought achievements are being accomplished, mainly by ectopically inducing reprograming via the four Yamanaka factors: Oct4, Sox2, Klf4 and c-Myc (OSKM) (Takahashi & Yamanaka, 2006). From resetting ageing hallmarks of cells from centenarian individuals (Lapasset et al, 2011) to ameliorating age associated hallmarks in aged organism in vivo (Ocampo et al, 2016;Sarkar et al, 2020;Rodríguez-Matellán et al, 2020;Lu et al, 2020). All these new scenarios are difficult to explain with most of the long-time proposed models of ageing, especially the damage-based models of ageing, but are very easily explainable by the model presented in this paper: ageing as an epigenetic information-based phenomenon and epigenetic reprograming as a regain access to an always kept information.…”
Section: Experimental Observations In Accordance With the Proposed Modelmentioning
confidence: 99%
“…Through epigenetic reprograming some never before thought achievements are being accomplished, mainly by ectopically inducing reprograming via the four Yamanaka factors: Oct4, Sox2, Klf4 and c-Myc (OSKM) (Takahashi & Yamanaka, 2006). From resetting ageing hallmarks of cells from centenarian individuals (Lapasset et al, 2011) to ameliorating age associated hallmarks in aged organism in vivo (Ocampo et al, 2016;Sarkar et al, 2020;Rodríguez-Matellán et al, 2020;Lu et al, 2020). All these new scenarios are difficult to explain with most of the long-time proposed models of ageing, especially the damage-based models of ageing, but are very easily explainable by the model presented in this paper: ageing as an epigenetic information-based phenomenon and epigenetic reprograming as a regain access to an always kept information.…”
Section: Experimental Observations In Accordance With the Proposed Modelmentioning
confidence: 99%
“…Many authors have suggested that epigenetic mechanisms may play a role in controlling lifespan and aging [7][8][9][10][11][12][13][14][15] . The role of epigenetics in mammalian aging is underscored by recent studies demonstrating age reversal through (transient) epigenetic reprogramming with Yamanaka factors [16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…The consequence of this phenomenon is a significant reduction in the formation of scar tissue during regeneration [ 184 ]. Recently, Rodríguez-Matellán et al demonstrated, with the i4F-B model, that a cyclic induction three days per week by 2mg/mL of doxycycline improved cognitive functions in mice, with a positive correlation between an increase scored in object recognition memory test and the level of OSKM expression [ 185 ].…”
Section: New Strategies In Regenerative Medicine To Rejuvenate Cells and Tissuesmentioning
confidence: 99%
“…Furthermore, epigenetics seems to play an important role in the regeneration phenomenon, as the inhibition of TET1 and TET2 DNA demethylase acts as a barrier and prevents any restoration. Epigenetic reorganizations involved in transient reprogramming are the widely considered to be the driving force behind the global rejuvenation phenomenon observed both in vitro and in vivo [ 181 , 185 , 186 , 188 , 189 ].…”
Section: New Strategies In Regenerative Medicine To Rejuvenate Cells and Tissuesmentioning
confidence: 99%